2000
DOI: 10.1902/annals.2000.5.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Bone‐Implant Complex. Results of Longitudinal Testing to 60 Months With the Periotest Device on Endosseous Dental Implants

Abstract: Conclusions of the study are as follows: 1) PTVs are influenced by bone quality and surface coating of the implant; 2) the PTVs at the time of uncovering provide the best estimate of a clinically acceptable PTV for that bone-implant complex; 3) while the PTVs for any bone-implant complex may fluctuate +/- 1.0 around the uncovering PTV during routine healing and loading of the implant, a consistent shift toward a positive PTV that approaches "0" should be cause for concern that the bone-implant complex may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Another group correlated the same techniques and their results show a different change of PTVs over time in densities 1 and 2 compared with 3 and 4, which could indicate a better bone‐to‐implant contact over time in better bone densities (Morris et al 2003). A similar finding was published in Truhlar et al (2000); these authors added that hydroxyapathite‐coated implants became less stable over time in contrast with non‐coated implants, which showed an improvement in stability over time. However, PTV values at implant placement and thereafter should be better correlated with an objective bone density classification to obtain more specified information.…”
Section: Resultssupporting
confidence: 76%
“…Another group correlated the same techniques and their results show a different change of PTVs over time in densities 1 and 2 compared with 3 and 4, which could indicate a better bone‐to‐implant contact over time in better bone densities (Morris et al 2003). A similar finding was published in Truhlar et al (2000); these authors added that hydroxyapathite‐coated implants became less stable over time in contrast with non‐coated implants, which showed an improvement in stability over time. However, PTV values at implant placement and thereafter should be better correlated with an objective bone density classification to obtain more specified information.…”
Section: Resultssupporting
confidence: 76%
“…It has been shown that in a clinical setting, following implantation, several cell types migrate towards the implant surface including endothelial cells, osteoblasts and stem cells (Khalil et al, 2011). This is a very important step for osteoinduction and over time, this accumulation at the implant surface will enhance implant stability and its success (Javed et al, 2013, Truhlar et al, 2000). …”
Section: Discussionmentioning
confidence: 99%
“…As for bone quality and quantity, we did not include enough patients with bone quality grade 4 (0 patients) and bone quantity grade D (one patient). This patient category was not willing to participate in the present study since informed of increased risks that were reported in previous studies (Truhlar et al 2000).…”
Section: Discussionmentioning
confidence: 99%